Dynamic acetylation of lysine-4-trimethylated histone H3 and H3 variant biology in a simple multicellular eukaryote. - Hsu, D; Chubb, JR; Muramoto, T; Pears, C; Mahadevan, L (Oxford University Press, 2012)
Dynamic acetylation of all lysine-4-trimethylated histone H3 is a complex phenomenon involved in Immediate-early gene induction in metazoan eukaryotes. Higher eukaryotes express repeated copies of three closely related H3 variants, inaccessible to genetic analysis. We demonstrate conservation of these phenomena in Dictyostelium which has three single-copy H3 variant genes. Although dynamic acetylation is targeted to two H3 variants which are K4-trimethylated, K9-acetylation is preferentially targeted to one. In cells lacking Set1 methyltransferase and any detectable K4-trimethylation, dynamic acetylation is lost demonstrating a direct link between the two. Gene replacement to express mutated H3 variants reveals a novel interaction between K4-trimethylation on different variants. Cells expressing only one variant show defects in growth, and in induction of a UV-inducible gene, demonstrating the functional importance of variant expression. These studies confirm that dynamic acetylation targeted to H3K4me3 arose early in evolution and reveal a very high level of specificity of histone variant utilization in a simple multicellular eukaryote.